KEPERCAYAAN DIRI DALAM PERSPEKTIF PSIKOLOGI KEPRIBADIAN PADA SITUASI PRESENTASI KELAS - Habibie Febri Arrafi; Sri Nurhayati Selian (As-Sulthan Journal of Education, 2026)
This study aims to examine students' self-confidence in classroom presentations from a personality psychology perspective. This study used a descriptive qualitative method involving three students who actively participated in lectures and had presentation experience. Data were collected through interviews, observations, and documentation to obtain an in-depth picture of the students' experiences. The results showed that most students experienced high levels of anxiety and nervousness, especially during their first presentation in front of a class, characterized by physical symptoms such as a trembling voice and lack of eye contact. Student self-confidence was influenced by several key factors: mastery of the material, experience or frequency of presentations, and social support from lecturers and peers. Good mastery of the material was associated with increased self-efficacy, thereby reducing negative thoughts and fear. Furthermore, students employed various strategies such as independent practice, review of the material, presentation simulations, and relaxation techniques to manage anxiety. Therefore, self-confidence is not an innate ability but can be developed through practice, experience, and a positive and ongoing environmental support.